Memos to the president : a guide through macroeconomics for the busy policymaker - Schultze, Charles L. (Brookings Institution, 1992)
When policymakers are in need of economic advice, professional economists are never far away. Policymakers, journalists, and citizens all rely on experts to explain various economic developments and policy proposals. While it is fortunate that experts are close at hand, those concerned with choosing or evaluating economic policies should themselves have an understanding of how the economy works. Unfortunately, many policymakers and interested citizens currently lack such knowledge; and they need to know at the least the basics of macroeconomics to make informed decisions on their own. In this.
Keywords: Macroeconomics.; United States -- Economic policy.; Macroéconomie.; États-Unis -- Politique économique.; POLITICAL SCIENCE / American Government / Executive Branch; Economic policy; Macroeconomics; United States; Makroökonomie; Politikberatung; Wirtschaftspolitik; USA; Economische politiek.; Macro-economie.; ECONOMIC POLICY.; UNITED STATES.; MACROECONOMICS.